2020
DOI: 10.1002/adsu.202000037
|View full text |Cite|
|
Sign up to set email alerts
|

Renewable Energy from Wildflowers—Perennial Wild Plant Mixtures as a Social‐Ecologically Sustainable Biomass Supply System

Abstract: A growing bioeconomy requires increasing amounts of biomass from residues, wastes, and industrial crops for bio‐based products and bioenergy. There is much discussion about how industrial crop cultivation could promote social–ecological outcomes such as environmental protection, biodiversity conservation, climate change adaptation, food security, greenhouse gas mitigation, and landscape appearance. In Germany, maize (Zea mays L.) is the main biogas substrate source, despite being associated with problems such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 290 publications
0
19
0
Order By: Relevance
“…The application of ammonium depots and nitrification inhibitors can reduce the amount of nitrogen fertilizer used, thereby decreasing both the risk of nitrate leaching, and greenhouse gas emissions from the field and from the upstream fertilizer production [131]. Promoting biodiversity and natural ecosystem processes also enhances many aspects of cultural services (see Table 2) [171,[260][261][262]. However, refraining from CSPs can also lead to a deterioration in crop supply services and environmental disadvantages if yield losses cannot be compensated by crop management measures as described above in Section 4.2 A significant decrease in crop yield because of the system conversion would have a negative impact on the environmental efficiency of crop production, because the environmental burdens would be attributed to lower output [130,[261][262][263][264][265].…”
Section: Mineral-ecological Cropping Systems From the Perspective Of Ecosystem Servicesmentioning
confidence: 99%
“…The application of ammonium depots and nitrification inhibitors can reduce the amount of nitrogen fertilizer used, thereby decreasing both the risk of nitrate leaching, and greenhouse gas emissions from the field and from the upstream fertilizer production [131]. Promoting biodiversity and natural ecosystem processes also enhances many aspects of cultural services (see Table 2) [171,[260][261][262]. However, refraining from CSPs can also lead to a deterioration in crop supply services and environmental disadvantages if yield losses cannot be compensated by crop management measures as described above in Section 4.2 A significant decrease in crop yield because of the system conversion would have a negative impact on the environmental efficiency of crop production, because the environmental burdens would be attributed to lower output [130,[261][262][263][264][265].…”
Section: Mineral-ecological Cropping Systems From the Perspective Of Ecosystem Servicesmentioning
confidence: 99%
“…In addition to common PECs such as willow [13,14], Miscanthus [15,16], Sida [17,18], switchgrass [19,20] and cup plant [21,22], the cultivation of perennial wild plant mixtures (WPMs) is becoming increasingly important in Germany [23]. The cultivation of WPMs enables farms to specifically contribute to the promotion of biodiversity through a high number of flowering wild plant species and, at the same time, gain significant biomass yields for bioenergy production [24,25]. Therefore, in some federal states, WPM cultivation is or will be subsidized, for example within the support program for agri-environment, climate protection and animal welfare ("FAKT", part of the Common Agricultural Policy) by up to EUR 500 per hectare per year [26].…”
Section: Introductionmentioning
confidence: 99%
“…Surveys with farmers who have first-hand experience of WPM cultivation for several years have shown that common tansy is one of these important yield-relevant species and that WPMs help to increase biodiversity in the agroecosystem [33,34]. It is currently unknown for how long common tansy can be cultivated until biomass yields decrease and are no longer profitable [24]; however, it is likely that common tansy can persist for longer than five years because it has great self-seeding potential. Due to the revised regulations for PEC in several German states, it will also be possible for farmers to cultivate WPMs for longer than five years without losing the arable status of the fields on which the WPMs are grown.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a continuous increase in the demand for bioenergy and biofuel has been observed 1 . Biogas and biomethane obtained through the conversion of biomass crops and organic residues could contribute to a reduction in the dependence on fossil fuels 2 . The biomethane obtained could be used as fuel for transport or for the production of electrical and thermal energy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Biogas and biomethane obtained through the conversion of biomass crops and organic residues could contribute to a reduction in the dependence on fossil fuels. 2 The biomethane obtained could be used as fuel for transport or for the production of electrical and thermal energy. Furthermore, the digestate could be applied to soils as organic fertilizer.…”
mentioning
confidence: 99%